Global Implications of Recent Innovations in U.S. Collective Bargaining - Cutcher-Gershenfeld, Joel; Power, Donald; McCabe-Power, Maureen (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
This paper deals with recent innovations in cooperative forms of collective bargaining. The authors begin by reviewing the wide range of highly cooperative approaches to negotiations. They then focus on a fairly comprehensive model, which is termed "target-specific bargaining". Finally, they explore some of the cross-cultural implications associated with applying the new forms of bargaining outside the North American context in two very different countries, Poland and South Africa.